Treatment Seeking Behavior and Health Care Expenditure Incurred for Hypertension Among Elderly in Urban Slums of Belgaum City - Sulakshana S Baliga; Praveen S Gopakumaran; Sangappa M Katti; Maheshwar D Mallapur (Medsci Publications, 2013)
Background: Hypertension is the commonest cardiovascular disorder, among elderly population .It is evident that the urban poor living in slums has poor access to healthcare, partly related to their poor purchasing ability. Present study was undertaken to determine treatment seeking behavior and health expenditure incurred among elderly hypertensive. Objectives: To determine treatment seeking behavior and health expenditure incurred for hypertension among elderly. Material and methods: A Cross sectional study was conducted among elderly population aged 60 years and above in three slums of urban health centre Ram Nagar, Belgaum. Results: Out of the 336 elderly population studied, 174(52%) were found to be hypertensive. Of the 174 hypertensive's, 146 were found to be known hypertensive's. Among the known hypertensive patients only 41 (28%) took regular treatment. High level of out of pocket spending by elderly is observed by way of purchase of medicines, high cost of hospitalization of varying length and charges for diagnostic services. Conclusion: With reduced ability to generate resources, the elderly lack basic needs that affect their health status. Emphasis for an effective health policy for the elderly is recommended.